Diversity of urinary tract infection bacteria in children in Indonesia based on metagenomic approach - GRACE CHRISTINE; SRI BUDIARTI; INDRI ASTUTI (Society for Indonesian Biodiversity, 2018)
Christine G, Budiarti S, Astuti RI. 2018. Diversity of urinary tract infection bacteria in children in Indonesia based on metagenomic approach. Biodiversitas 19: 1375-1381. Urinary tract infection (UTI) is a common bacterial infection in childhood in both males and females. The infection is usually caused by bacterial invasion of the urinary tract including the lower and the upper urinary tract. In Indonesia, to the best our knowledge, the diversity of urinary tract infection bacteria has not been reported yet. Therefore, the aims of this study were to identify the diversity of both culturable and unculturable bacteria in children diagnosed with UTI. In this study, urine samples were obtained from different age groups ranging 6-17 years. Analysis of 16S rRNA gene sequence showed eight culturable isolates (SBU1, SBU2, SBU3, SBU4, SBU5, SBU6, SBU7, SBU8) are closely related to Escherichia coli, Klebsiella pneumoniae, Enterobacter aerogenes, Citrobacter sp. and Acinetobacter sp. with maximum identity up to 98-99%. Diversity of unculturable bacteria community based on 16S rRNA gene was represented by 9 DGGE (Denaturing Gradient Gel Electrophoresis) bands. The nine respective bands showed the similarity ranging from 84 up to 96% with Klebsiella sp, Escherichia sp., Lactococcus lactic, Shigella flexneri and uncultured bacterium. Based on phylogenetic analysis, all culturable isolates belong to phylum Proteobacteria, which is dominated by family of Enterobacteriaceae. Interestingly, by using metagenomic approach, it is observed that bacteria belong to phylum Firmicutes were found in the UTI-diagnosed patients, in addition to those bacterial isolates from phylum Proteobacteria. To our knowledge, this is the first study to report the occurrence of Firmicutes and Proteobacteria in UTI-diagnosed patients in Indonesia.